2018
DOI: 10.3390/molecules23112833
|View full text |Cite
|
Sign up to set email alerts
|

3,5-Diethoxy-3′-Hydroxyresveratrol (DEHR) Ameliorates Liver Fibrosis via Caveolin-1 Activation in Hepatic Stellate Cells and in a Mouse Model of Bile Duct Ligation Injury

Abstract: Hepatic stellate cells (HSCs) are involved in the pathogenesis of liver fibrosis. Resveratrol, 3,5,4′-trihydroxystilbene, is a dietary polyphenol found in natural food products. Here, we evaluated the anti-proliferative effects of a synthetic resveratrol derivative, 3,5-diethoxy-3′-hydroxyresveratrol (DEHR), on HSCs. Flow cytometry and Western blot analyses showed that DEHR induces apoptosis through the upregulation of cleaved caspase-3 and poly (ADP-ribose) polymerase expression and reduction in the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Astaxanthin was shown to inhibit liver fibrosis via HSC inactivation and the decreased formation of ECM in carbon tetrachloride (CCl 4 ) and bile duct ligation mouse models [ 75 ]. Similar results were also reported for treatments with curcumin [ 76 ], blueberry [ 77 ], silymarin [ 78 ], 3, 5-diethoxy-3′-hydroxyresveratrol [ 79 ], quercetin [ 80 ], epigallocatechin-3-gallate [ 81 ], coffee [ 82 ], and vitamins [ 83 ]. Additionally, Kuo et al suggested that the marine extract from a gorgonian coral Pinnigorgia sp.…”
Section: Discussionsupporting
confidence: 76%
“…Astaxanthin was shown to inhibit liver fibrosis via HSC inactivation and the decreased formation of ECM in carbon tetrachloride (CCl 4 ) and bile duct ligation mouse models [ 75 ]. Similar results were also reported for treatments with curcumin [ 76 ], blueberry [ 77 ], silymarin [ 78 ], 3, 5-diethoxy-3′-hydroxyresveratrol [ 79 ], quercetin [ 80 ], epigallocatechin-3-gallate [ 81 ], coffee [ 82 ], and vitamins [ 83 ]. Additionally, Kuo et al suggested that the marine extract from a gorgonian coral Pinnigorgia sp.…”
Section: Discussionsupporting
confidence: 76%
“…After centrifugation at 900× g for 1 min, the supernatant was mixed with a luciferase reagent. Afterwards, the amount of ATP was measured using the ATP Bioluminescence Assay Kit CLS II (Roche, Penzberg, Germany) [25].…”
Section: Methodsmentioning
confidence: 99%
“…12,13 The cytoprotective effect of HO-1 could have several distinct underlying mechanisms, including degradation of heme to the antioxidant bilirubin; coordinated induction of ferritin, which chelates the pro-oxidant free iron; and release of CO, which exerts significant antioxidant effects. 12,13…”
mentioning
confidence: 99%